Solution of 3D nonviscous compressible gas equations on unstructured meshes using the distributed computing approach - Evstigneev, N.M. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2007)
A numerical method for solving the 3D nonviscous compressible gas equations on unstructured tetrahedral meshes is proposed. The method can be used for any complex geometry as well as to study any flow regimes. The numerical scheme of integration is based on the finite-volume modified E-CUSP approximate Riemann solver. For a higher-order approximation, a TVD-limiter approach is used. The computation speedup can be achieved by using the distributed computing on a TCP-IP network with cheap and easy-available PCs. Numerical and experimental results are compared for a special wing profile for the transonic regime of flow. The numerical method was proved to be accurate, flexible, and efficient and can be used to solve a wide range of complicated inflow and overflow aerodynamic problems.